Me and my dog - Dahl, Michael; Persico, Zoe (North Mankato, Minnesota Pictrue Window Books, a Capstone imprint, 2016)
A young boy describes all the things he can do with his dog--but also the things he should not do
English stories
1 2 13 15
NEW_ZTN_GN
Keywords: Dogs -- Fiction; Dogs -- Juvenile fiction; Play -- Fiction; Play -- Juvenile fiction